The Level of Physical Strength Towards The Endurance of Volleyball Players at Senior High School 2 Martapura Using The Pacer Test - Muhammad Hamka Ferdiansyah; Mita Erliana; Norma Anggara (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of this study was to determine the level of physical endurance of students who participate in extracurricular volleyball at Senior High School 2 Martapura. The method used in this study is quantitative descriptive. The sample and population amounted to 26 students using the total sampling technique, with the pacer test instrument. The results of the study on the level of physical strength towards the endurance of volleyball players at Senior High School 2 Martapura using the pacer test showed that the physical strength endurance of 26 male and female students, there were 7 sons (54%) and 12 daughters (92%) including very low classification, 3 sons (23%) and 1 daughter (8%) are classified as low, 3 sons (23%) and 0 daughters (0%) are classified as sufficient, and none of the male or female students (0%) were classified as good or very good. Conclusion of the research results (1) based on the results of this research, the average level of physical endurance of male and female students who participate in extracurricular volleyball at Senior High School 2 Martapura is very low. (2) Lack of physical training programs provided to students who participate in extracurricular volleyball at Senior High School 2 Martapura. Physical endurance is very influential when performing techniques in volleyball, so there are obstacles when performing certain techniques.